« Nous qui sommes sans passé, les femmes ». À la recherche d’une généalogie féministe dans les pages de Vindicación Feminista - Claudia Jareño Gila (Cahiers de Civilisation Espagnole Contemporaine)
Since its creation magazine Vindicación Feminista (1976-1979) was committed to the history of Iberian feminism and in particular to the history of republican women due to its ideological affinities and personal ties Its unambiguously attachment to the republican cause from its first number legitimized its position as a feminist magazine. In addition, Vindicación Feminsita was a means of establishing an historical justice with those who preceded it and their fights hidden by the Franco’s dictatorship. In the Transition context filled with strong socio-political transformations, issues related to memory and to past struggles for social transformation gained importance through the pages of Vindicación Feminista allowing to a rich present-past dialogue being established not without contradictions.